Identification and functional characterization of AcMYB113 in anthocyanin metabolism of Aesculus chinensis Bunge var. chinensis leaves - Liu, Minmin (Plant physiology and biochemistry : PPB, 2023)
Copyright © 2023 Elsevier Masson SAS. All rights reserved.